Determinants of the growth hormone nadir during oral glucose tolerance test in adults. Issue 1 (July 2019) - Schilbach, Katharina; Gar, Christina; Lechner, Andreas; Nicolay, Shiva Sophia; Schwerdt, Laura; Haenelt, Michael; Dal, Jakob; Jørgensen, Jens-Otto Lunde; Störmann, Sylvère; Schopohl, Jochen; Bidlingmaier, Martin
Abstract : Objective: Growth hormone (GH) nadir (GHnadir ) during oral glucose tolerance test (OGTT) is an important tool in diagnosing acromegaly, but data evaluating the need to adjust cut-offs to biological variables utilizing today's assay methods are scarce. We therefore investigated large cohorts of healthy subjects of both sexes to define normal GHnadir concentrations for a modern, sensitive, 22 kD-GH-specific assay. Design: Multicenter study with prospective and retrospective cohorts (525 healthy adults: 405 females and 120 males). Methods: GH concentrations were measured by the IDS-iSYS immunoassay after oral application of 75 g glucose. Results: GHnadir concentrations (µg/L) were significantly higher in lean and normal weight subjects (group A) compared to overweight and obese subjects (group B); (males (M): A vs B, mean: 0.124 vs 0.065, P = 0.0317; premenopausal females without estradiol-containing OC (OC-EE) (FPRE ): A vs B, mean: 0.179 vs 0.092, P < 0.0001; postmenopausal women (FPOST ): A vs B, mean: 0.173 vs 0.078, P < 0.0061). Age, glucose metabolism and menstrual cycle had no impact on GHnadir . However, premenopausal females on OC-EE (FPREOC ) exhibited significantly higher GHnadir compared to all other groups (all P < 0.0001). BMI had no impact on GHnadir in FPREOC (A vs B, mean: 0.624 vs 0.274, P = 0.1228). Conclusions: BMI, sex and OC-EE intake are the major determinants for the GHnadir during OGTT in healthy adults. Using a modern sensitive GH assay, GHnadir concentrations in healthy subjects are distinctly lower than cut-offs used in previous guidelines for diagnosis and monitoring of acromegaly.